1986
DOI: 10.1111/j.1365-2273.1986.tb00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and clinical aspects of carbon as a middle ear prosthesis

Abstract: The biocompatibility of vitreous carbon and carbon fibre reinforced carbon (CFRC) as middle ear implants was investigated. In separate animal model systems, vitreous carbon was implanted in the middle ear of 20 DA rats for up to 6 months, whilst 3 varieties of CFRC (basic or crude, ultrasonically cleaned, glazed) were implanted in 98 guinea-pig middle ears for up to 4 months. Tissue reactions to implantation were assessed by means of stereoscopic and standard light microscopy, and scanning electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
(1 reference statement)
0
4
0
1
Order By: Relevance
“…12 Furthermore, in a small clinical study using carbon bre reinforced carbon as the ossicular prosthesis, Blayney et al reported a 40 per cent extrusion rate at nine months and a further eight per cent with in ammatory responses around the implant. 50 Titanium (Ti) was established as an excellent biocompatible material by Branemark in the 1970s. 51 It was rst introduced as an alloplastic material for ossiculoplasty in 1993.…”
mentioning
confidence: 99%
“…12 Furthermore, in a small clinical study using carbon bre reinforced carbon as the ossicular prosthesis, Blayney et al reported a 40 per cent extrusion rate at nine months and a further eight per cent with in ammatory responses around the implant. 50 Titanium (Ti) was established as an excellent biocompatible material by Branemark in the 1970s. 51 It was rst introduced as an alloplastic material for ossiculoplasty in 1993.…”
mentioning
confidence: 99%
“…A wide variety of implants, including artificial joints, plates and screws for treatment of fractures, maxillofacial implants, and middle ear implants have been developed, and some of these are now clinically applied. [76][77][78]…”
Section: Carbon Fiber/polymer Compositesmentioning
confidence: 99%
“…Bei Humanexplantaten fanden sich mehrkernige, fremdkörperhaltige Riesenzellen, was als Fremdkörperreaktion mit Degradation des Implantates angesehen wird [97]. Reiner Glaskohlenstoff als Implantatmaterial ist wegen starker Fremdkörperreaktionen mit konsekutiver Abstoßung in Tierversuchen und im klinischen Einsatz nicht zu empfehlen [98,99]. Flex H/A ist ein Komposit, welches aus Hydroxylapatit und Silastik zu gleichen Teilen besteht.…”
Section: Biotolerante Materialienunclassified